2020
DOI: 10.1177/0957650920976666
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic optimization of a SCO2 radial-inflow turbine based on an improved simulated annealing algorithm

Abstract: Supercritical carbon dioxide plays a vital role in the development of power generation applications. It owns the characteristics of high density and low viscosity, which can ensure a compact structure for turbomachinery. With the blossom of optimization algorithm, an interdisciplinary research which applies optimization method to a traditional design process of turbomachinery can accelerate the course and promote the validity by leaps and bounds. We improve the traditional simulated annealing algorithm and est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The tip clearance loss is the most significant loss for turbines with a output power of a few hundred kW, while the passage, stator and outlet kinetic losses account for a greater proportion for higher power turbines. Wang et al improved the simulated annealing algorithm (SAA) and established the optimization process of a kW scale S-CO2 turbine, including rotor meridian plane and nozzle profile optimization [68]. They achieved a maximum isentropic efficiency improvement of 4.94% in improved simulated annealing algorithm (ISAA) calculations.…”
Section: S-co2 Power Cyclementioning
confidence: 99%
“…The tip clearance loss is the most significant loss for turbines with a output power of a few hundred kW, while the passage, stator and outlet kinetic losses account for a greater proportion for higher power turbines. Wang et al improved the simulated annealing algorithm (SAA) and established the optimization process of a kW scale S-CO2 turbine, including rotor meridian plane and nozzle profile optimization [68]. They achieved a maximum isentropic efficiency improvement of 4.94% in improved simulated annealing algorithm (ISAA) calculations.…”
Section: S-co2 Power Cyclementioning
confidence: 99%
“…Yi et al 7 developed a solution program for 3D viscous flow field and a numerical optimization program using response surface method and simulated annealing algorithm, and then carried out numerical optimization design for transonic pressure maneuverable blades. Wang et al 8 improved the traditional simulated annealing algorithm to optimize the rotor meridian plane and endwall profile of the nozzle. Compared with the traditional simulated annealing algorithm and genetic algorithm, it was found that the improved simulated annealing algorithm saves calculation time and increases the isentropic efficiency by 4.94%.…”
Section: Introductionmentioning
confidence: 99%
“…In the current digital era, Indoor Scene Coloring Design (ISCD) plays a crucial role in architectural design, film production, game development, and more [1]. With the rise of virtual reality technology and consumers' high requirements for visual experience, interior scene coloring design has become more complex and the demand has increased [2].…”
Section: Introductionmentioning
confidence: 99%